Effect of the COVID-19 pandemic on maternal mortality and cesarean section rates among brazilian adolescents - Maite dos Santos Borges; Clarissa Suzart; Maria Paula Perroca Lipi; Fernanda Garanhani Surita; Diama Bhadra Vale; José Paulo de Siqueira Guida (International Journal of Adolescence and Youth)
Adolescent pregnancy poses a challenge due to clinical and social risks, increasing the likelihood of low adherence to prenatal care and violence. The COVID-19 pandemic significantly impacted obstetric care in Brazil, possibly increasing maternal death and caesarean section rates (CSR) in Brazilian adolescent pregnancies. We performed a cross-sectional study analysing births and maternal deaths in Brazil in 2019 (pre-pandemic) and 2021 (pandemic). Data were obtained from the Brazilian Panels of Monitoring Live Births and Maternal Mortality. Data on number of births, maternal mortality rate (MMR), and CSR were compared in both periods. There was a significant reduction in adolescent births during the pandemic (13.62% in 2021 vs. 14.72% in 2019). The MMR increased from 46.75 to 62.79 per 100,000 live births, due to respiratory infections (23.98% to 43.67%). The CSR increased from 38.39% to 40.25%. The results suggest an increase in CSR and MMR among Brazilian adolescents during COVID-19 pandemic.